Improving the Structural and Morphological Characteristic of Carboxymethyl cellulose (CMC) Via Additive ZnSe Nanoparticle - Hussein Kamil Mohammed; Zaid A. Hasan; Khalid Al-Ammar (International Journal of Computational and Experimental Science and Engineering, 2025)
The present study focuses on the preparation of Zinc selenide (ZnSe) doped Carboxymethyl cellulose (CMC) for utilization in various optoelectronic applications. X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), and field emission scanning electron microscopy (FESEM) were employed to analyze the structural and morphological characteristics. The XRD results indicated an amorphous nature for CMC, which transitioned to a polycrystalline structure upon the addition of high loading (8 wt.%) ZnSe nanoparticles. FTIR spectra confirmed a physical interaction between the ZnSe nanoparticles and the CMC polymer matrix. FESEM analysis revealed a uniform distribution of ZnSe nanoparticles throughout the CMC polymer matrix. These findings suggest that the CMC/ZnSe composite is appropriate for optoelectronic device applications.